Videoreport Italia 2004-05. - Bruciati, Andrea; De Cecco, Emanuela; Gorni, Mario; Molinari, Guido; Robecchi, Michele; Smarrelli, Marcello (Milano : Silvana Editoriale Spa Milano, 2006)
Alksne, Kristine ; Ancarani, Yuri ; Benassi, Elisabetta ; Benassi, Riccardo ; Bertocchi, Davide ; Biscotti, Rossella ; Boggeri, Dafne ; Casas, Carlos M. ; Cattaneo, Alice ; Cattani, Annalisa ; Cecchetti, Alex ; Chiasera, Paolo ; Chironi, Cristian ; Dojmi, Andrea ; Fliri, Michael ; Francesconi, Luca ; Frosi, Christian ; Gobbetto, Nicola ; Guidato, Alberto ; Kirchhoff, Thorsten ; Koike, Kensuke ; Lauretta, Francesco ; Linke, Armin ; Mangano, Domenico ; Marisaldi, Eva ; Martegani, Amedeo ; Martena, Annamaria ; Mezzaqui, Sabrina ; Migliora, Marzia ; Morgantin, Margherita ; Motti, Gianni ; Nark BKB ; Niccoli, Christian ; Orlando, Valerio Rocco ; Paci, Adrian ; Pobitzer, Klaus ; Previdi, Riccardo ; Rahimi, Farid ; Rapicavoli, Maria D. ; Rizzi, Mario ; Rossi, Sara ; de Serio, Gianluca e Massimiliano ; Shoggoth ; Sighicelli, Elisa ; Simeone, Marcello ; Terlizzi, Cosimo ; Trevisani, Luca ; Uni, Lucia ; Uzunovski, Nikola ; Vanzo, Marcella ; Vascellari, Nico ; Xhafa, Sislej ; ZimmerFrei ; Zuffi, Italo
biog., ind. tent., gr. tent. p. 170-219
Italiaans
Engels
Exhibition. Videoreport Italia 2004-05 (1). Exhibition. Videoreport Italia 2004-05 (2). GC.AC (Galleria comunale d'Arte Contemporanea) Monfalcone. 13.10.2006 - 01.11.2006. MAN (Museo d'Arte Provincia di Nuoro) Nuoro. 17.11.2006 - 10.12.2006.
boek